Vibrational Assignments and Analysis for 2-Benzimidazole Thione - Peri, B.; Mohan, S. (Asian Journal of Chemistry, 2012)
The Laser Raman and FTIR Spectra of 2-benizimidazole thione have been recorded in the region 4000-100 cm-1. The observed frequencies were assigned to different modes of vibrations on the basis of fundamental, combination and overtones and normal coordinate analysis assuming Cs point group symmetry. The potential energy distributions (PEDs) associated with each vibrational type is also reported. Further, based on the present assignments, a complete vibrational analysis was carried out for this compounds. The results are briefly discussed.